Added value of 3D echocardiography in the diagnosis and prognostication of patients with right ventricular dysfunction - Michael Randazzo; Francesco Maffessanti; Alekhya Kotta; Julia Grapsa; Roberto M. Lang; Karima Addetia (Frontiers in Cardiovascular Medicine, 2023)
Recent inroads into percutaneous-based options for the treatment of tricuspid valve disease has brought to light how little we know about the behavior of the right ventricle in both health and disease and how incomplete our assessment of right ventricular (RV) physiology and function is using current non-invasive technology, in particular echocardiography. The purpose of this review is to provide an overview of what three-dimensional echocardiography (3DE) can offer currently to enhance RV evaluation and what the future may hold if we continue to improve the 3D evaluation of the right heart.